Effect of experimental conditions on the grafting of maleic anhydride onto polyethylene in extruders - Machado, A. V. (2004)
This work investigates the effect of the operating conditions (set temperature and prescribed throughput) on the evolution of the MA grafted content on high density polyethylene along a co-rotating twin screw extruder. Samples were quickly removed from the extruder at relevant axial locations, quenched and subsequently characterized off-line. While grafting was monitored by FTIR, the residual peroxide was determined by gas chromatography. The results show a good correlation between residual peroxide and MA grafted content.